2007
DOI: 10.1093/pcp/pcl044
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Processes During the Formation of the Plant-Specific Dof Transcription Factor Family

Abstract: We found 19 putative genes for plant-specific Dof transcription factors in the moss Physcomitrella patens and one Dof gene in the green alga Chlamydomonas reinhardtii, but no identifiable Dof gene in the red alga Cyanidioschyzon merolae and the diatom Thalassiosira pseudonana, suggesting that the origin of the Dof transcription factors pre-dates the divergence of the green algae and the ancestors of terrestrial plants. The phylogenetic analyses contended that the Dof family in angiosperms formed through a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 25 publications
5
72
0
2
Order By: Relevance
“…All CDFs except CDF4 play redundant roles in repressing CO expression and photoperiodic flowering in Arabidopsis (Fornara et al 2009). Consistent with the hypothesis that in general, closely related Dof transcription factors share small amino acid motifs outside the highly conserved Dof DNA-binding domain (Lijavetzky et al 2003;MorenoRisueno et al 2007;Shigyo et al 2007;Yanagisawa 2002), all CDFs except CDF4 have conserved amino acid motifs in their C-terminal regions (Fornara et al 2009;Imaizumi et al 2005). Thus, these conserved amino acid motifs are characteristic of CDFs.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…All CDFs except CDF4 play redundant roles in repressing CO expression and photoperiodic flowering in Arabidopsis (Fornara et al 2009). Consistent with the hypothesis that in general, closely related Dof transcription factors share small amino acid motifs outside the highly conserved Dof DNA-binding domain (Lijavetzky et al 2003;MorenoRisueno et al 2007;Shigyo et al 2007;Yanagisawa 2002), all CDFs except CDF4 have conserved amino acid motifs in their C-terminal regions (Fornara et al 2009;Imaizumi et al 2005). Thus, these conserved amino acid motifs are characteristic of CDFs.…”
supporting
confidence: 60%
“…Dof transcription factors, which possess plant-specific Dof DNA-binding domains, are present in both vascular and non-vascular plants ( Moreno-Risueno et al 2007;Shigyo et al 2007) and play roles in a variety of biological processes in the plant kingdom (Sugiyama et al 2012;Yanagisawa 2002). Recently, a Dof transcription factor in Arabidopsis thaliana (Arabidopsis) was identified as a transcriptional repressor of CONSTANS (CO), which encodes a master regulator of photoperiodic gene expression and the floral transition from the vegetative phase to the reproductive phase (Imaizumi and Kay 2006;Samach and Coupland 2000;Song et al 2010;Valverde 2011); this factor was designated CYCLING DOF FACTOR 1 (CDF1).…”
mentioning
confidence: 99%
“…converged on genes encoding transcription factors of the plant-specific DOF (DNA-BINDING WITH ONE ZINC FIN-GER) family (Lijavetzky et al, 2003;Yanagisawa, 2002) because of the correlation between their molecular diversification and the functional differentiation of the plant body into physiologically distinct organs during evolution (Shigyo et al, 2007). Our findings suggest that expression of three DOF genes can be assigned to stages of preprocambial development that overlap with acquisition of the ATHB8 cell state.…”
Section: Expression Of Dof Genes In Seedling Organsmentioning
confidence: 65%
“…Therefore, to identify new preprocambial gene expression profiles, we interrogated an available global gene expression map of the Arabidopsis root (Birnbaum et al, 2003) to extract root vascular-specific gene expression datasets. We focused on genes encoding members of the DOF family of plant-specific transcription factors because their evolutionary diversification is associated with the compartmentalization of the plant body into separate organs (Shigyo et al, 2007). We found that nine of the 36 DOF genes in Arabidopsis (Lijavetzky et al, 2003;Yanagisawa, 2002) displayed a strong expression bias for root vascular cells (F i g .…”
Section: Resultsmentioning
confidence: 99%
“…It has been known for some time that AQPs are present in P. patens, a well-established model system for various biological and evolutionary processes in higher plants (Schaefer, 2002;Quatrano et al, 2007;Shigyo et al, 2007). Twelve putative AQP sequences were first identified in a homology screen of a P. patens EST library (Borstlap, 2002), five of which belong to the PIP (plasma membrane intrinsic proteins) family.…”
mentioning
confidence: 99%